2018
DOI: 10.1097/md.0000000000012133
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sternocleidomastoid muscle and suboccipital muscle soft tissue release on muscle hardness and pressure pain of the sternocleidomastoid muscle and upper trapezius muscle in smartphone users with latent trigger points

Abstract: Few studies have been performed regarding the reduction of pain in the upper trapezius (UT) muscle by applying interventions to the sternocleidomastoid (SCM) muscle, which is innervated by the same nerves.The purpose of this study was to investigate the effects of soft tissue release intervention on the SCM and suboccipital muscles with regard to muscle hardness and pressure pain threshold (PPT) of the SCM and UT muscles in smartphone users with latent myofascial trigger points (MTrPs) in the UT muscle.Sevente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 24 publications
1
16
0
2
Order By: Relevance
“…Few studies explored the influence of KT intervention on soft tissue hardness. Kim and Lee (2018) noted that the hardness of the upper trapezius muscle remarkably decreased and the PPT value substantially increased after applying the sternocleidomastoid muscle relaxation technique. Via magnetic resonance elastography, Wang et al (2019) observed the acute effects of KT intervention on a single side of the lumbar paraspinal muscle and found that the intervention reduced muscle stiffness near the taping area.…”
Section: Effects Of Kt Intervention On Soft Tissue Hardnessmentioning
confidence: 97%
“…Few studies explored the influence of KT intervention on soft tissue hardness. Kim and Lee (2018) noted that the hardness of the upper trapezius muscle remarkably decreased and the PPT value substantially increased after applying the sternocleidomastoid muscle relaxation technique. Via magnetic resonance elastography, Wang et al (2019) observed the acute effects of KT intervention on a single side of the lumbar paraspinal muscle and found that the intervention reduced muscle stiffness near the taping area.…”
Section: Effects Of Kt Intervention On Soft Tissue Hardnessmentioning
confidence: 97%
“…MT'nin kas sertliği üzerine etkileri, farklı popülasyonlarda ve farklı değerlendirme yöntemleri ile incelenmiştir. [26][27][28][29] Servikojenik baş ağrısında, servikal mobilizasyonunun servikal kas sertliği üzerine etkisinin "shear-wave elastografi (SWE)" ile incelendiği bir olgu çalışmasında, tek seans servikal mobilizasyondan sonra TRP kas sertliğinin azaldığı bildiril- miştir. 26 Park ve ark.…”
Section: Discussionunclassified
“…TRP kasında tetik noktaları bulunan akıllı telefon kullanıcılarında SKM ve suboksipital kaslara uygulanan yumuşak doku tekniklerinin kas sertliğine etkisini miyotonometrik bir cihaz ile incelemiş ve yumuşak doku tekniklerinin SKM ve TRP kas sertliğini azalttığını bulmuşlardır. 28 Miyotonometrik bir cihaz ile kas sertliğinin incelendiği başka bir çalışmada, eklem ve yumuşak doku tekniklerini içeren MT'nin miyofasiyal ağrı sendromlu bireylerin kas sertliğini akut olarak azalttığı belirtilmiştir. 29 13,30 Çalışmamızın diğer bir bulgusu ise 6 haftalık MT'nin boyun ağrısına bağlı özür şiddetini azalttığı yönündeydi.…”
Section: Discussionunclassified
“…It helps to move the head (extension and rotation) and the shoulders (shrugging, lowering, posterior tipping, bringing the scapulae closer together) (5). Also, The spinal accessory nerve innervates the sternocleidomastoid muscle (SCM) and runs underneath it or directly passes through the muscle belly, and thus, when MTrPs are created in the SCM from any microinjury it compresses and excites the nerve leading to pain that might be caused by ischemia in the UT muscle innervation (6). though, this complication has been taken into consideration in the treatment protocol by applying stretching techniques in the SCM muscle to decrease the load on the accessory nerve and make sure that the UT muscle has normal innervation.…”
Section: Introductionmentioning
confidence: 99%